EVALUASI SISTEM PENGELOLAAN DAERAH IRIGASI DI PROVINSI SULAWESI UTARA - Leo Hengky Kalesaran; Jailani ., Husain; Bobby V. J. Polii (Sam Ratulangi University, 2016)
The objectives of this research were: (1) to get the new information and knowledge about the irrigation area system management existing in North Sulawesi Province, (2) to study about the complexity aspects of the irrigation area system management, and (3) to know the model of irrigation area management system in North Sulawesi Province, and to propose the alternative one. This research was designed as descriptive one. Data and information were collected through in-depth interviews and by questionnaires. Twenty one representatives of irrigation stakeholders in North Sulawesi were selected as respondents by using purposive sampling method. The result showed that (1) the distribution and management of irrigation area in North Sulawesi Province was determined by the criteria and status authority stated in the Ministry of Public Work and Public Housing of Indonesia Regulation which consisted of: Irrigation area authorized to the central government, provincial government, and regency or municipal government. It was found that 25.162 Ha from 80.792 Ha of potential irrigated land had not been converted as irrigated land. (2) From the two main components of irrigation areas, which are irrigation infrastructure, and irrigation land, it was found that the government more focused their activities and budget in supporting the irrigation infrastructure operation and maintenance, while other factors regarding to the management of irrigation land, such as water catchment area condition, the local commission of irrigation, regulation system, inter-sector coordination system, the direction of sector policies development, and the environment and sustainable development concerns had not got enough attention, and (3) The model of irrigation area management system existing in North Sulawesi Province, was still a â€˜close systemâ€. It is recommended to change this to be an â€œopen systemâ€ so that other related sectors can get involved.*ghmk*